Inhibiting wax deposition using palm oil additives - Ragunathan, T. (Offshore Technology Conference, 2020)
Among the various flow assurance problems that the petroleum industry faces, the deposition of paraffin waxes on to the wall of the pipeline is the most challenging. The challenge arises when the crude oil temperature decreases below the wax appearance temperature (WAT) which leads to the wax crystal in the crude oil to crystallize. An efficient method in remedying paraffin wax deposition is the utilization of chemical inhibitors. However, currently used chemical inhibitors are costly and environmentally harmful if a spillage occurs. Therefore, the use of biodegradable or environmently friendly inhibitors as potential chemical inhibitors are being studied by various researchers. This study investigated oleic acid, poly (ethylene-co-vinyl acetate) (EVA) and triethanolamine (TEA) as inhibitors that perform based on the van der Waals intermolecular interaction between the main wax component molecule eicosane C20H42 using the molecular dynamics simulation (MD) procedure via Material Studio 8.0 software package. In order to analyse the desired structural property which is the Radial Distribution Function (RDF), COMPASS force field was used. The RDF and g(r) function portrayed the functional atoms which aid in inhibiting the agglomeration and crystallization of the wax crystal formation. The presence of a carbonyl oxygen in oleic acid plays a vital role to inhibit the wax formation through the van der Waals interaction between active hydrogen atoms in eicosane molecule. Therefore, the chances of wax inhibition in eicosane is higher by introducing oleic acid as an inhibitor as compared to EVA and TEA. The results were then validated experimentally utilizing a cold finger technique under static condition. Copyright Â© 2020, Offshore Technology Conference.